2005
DOI: 10.1002/app.21686
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic degradation of solutions of poly(vinyl acetate) in tetrahydrofuran

Abstract: ABSTRACT:The ultrasonic degradation of poly(vinyl acetate) (PVAc) solutions was carried out in tetrahydrofuran (THF) at 20, 25, 30, and 35°C to investigate the effects of the temperature and solution concentration on the rate of degradation. The degradation kinetics were studied with viscometry. The calculated rate constants indicated that the degradation rate of the PVAc solutions decreased as the temperature and solution concentration increased. The calculated rate constants were correlated in terms of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Models based on continuous distribution kinetics have been developed to study the ultrasonic degradation of polymers [20–22]. The ultrasonic degradation of polymers such as polystyrene [11], polyethyleneoxide [20], polyvinyl acetate [9, 21, 23], polyvinyl alcohol [24], polybutadine [25], polypropylene [25, 26], poly(vinyl‐pyrrolidone) [27, 28], poly(acrylates) [29], dextran [30], poly(methyl methacrylate) [31], low density polyethylene [32], poly(alkyl methacrylate) [33], poly(alkyl acrylate) [34] and hydrogels [35, 36]. Thus, although the degradation of a wide variety of homopolymers has been studied, there have been only studies on two sets of copolymers: styrene‐butadiene copolymers [14] and the copolymers of poly(methyl methacrylate ‐co‐ alkyl acrylate) [37].…”
Section: Introductionmentioning
confidence: 99%
“…Models based on continuous distribution kinetics have been developed to study the ultrasonic degradation of polymers [20–22]. The ultrasonic degradation of polymers such as polystyrene [11], polyethyleneoxide [20], polyvinyl acetate [9, 21, 23], polyvinyl alcohol [24], polybutadine [25], polypropylene [25, 26], poly(vinyl‐pyrrolidone) [27, 28], poly(acrylates) [29], dextran [30], poly(methyl methacrylate) [31], low density polyethylene [32], poly(alkyl methacrylate) [33], poly(alkyl acrylate) [34] and hydrogels [35, 36]. Thus, although the degradation of a wide variety of homopolymers has been studied, there have been only studies on two sets of copolymers: styrene‐butadiene copolymers [14] and the copolymers of poly(methyl methacrylate ‐co‐ alkyl acrylate) [37].…”
Section: Introductionmentioning
confidence: 99%
“…When high‐intensity ultrasonic irradiation is subjected to polymer solution, the main‐chain scission of polymer occurs and consequently the molecular weight is decreased. The macroradicals formed through the chain scission of polymer can be terminated by radical scavengers to produce the polymers with controlled molecular weight and molecular weight distribution 9–12…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] It has been suggested that ultrasonic irradiation of a polymer solution will proceed with induction of cavitation in the solution which will corrupt to form short-living high-temperature/pressure spots, and the polymer molecules will then be decomposed either physically by the shear forces created in corrupting walls or chemically by radical reaction with solvent or dissolving gas.…”
Section: Introductionmentioning
confidence: 99%